Is task-based language teaching in evidence in tertiary level English as an additional language? An exploration into teachers’ practices related to task uses - ling ling Guan (Research in English Language Pedagogy, 2022)
Over the last two decades, task-based language teaching (TBLT) has been promoted as more effective for language acquisition than conventional communicative pedagogic practices in a variety of literature. However, it is unclear whether TBLT principles are integrated into English as additional language (EAL) teachers’ beliefs and how they made use of ideas announced in the TBLT literature at tertiary level in New Zealand. This exploratory study investigated whether TBLT is evident in three tertiary EAL teachers’ classes and how these teachers used tasks in language classes in New Zealand. Repeated semi-structured interviews and classroom observations were employed in this case study research. A key finding is that teachers were using a Communicative Language Teaching model rather than what they claimed to be TBLT. Furthermore, teachers did not prioritize a particular task feature, which was to have a non-linguistic outcome at the end of the task. This study contributes to our understanding of teachers’ beliefs and practices with regard to TBLT in New Zealand.